2014
DOI: 10.1002/j.2161-0045.2014.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors Supporting African Immigrant Students' Career Development: A Case Study

Abstract: School counselors play a critical role in preparing adolescent immigrant students to be college and career ready by attending to the complex variables that promote and inhibit career development. This article provides an illustrative case study of a Somali immigrant student's educational journey to highlight the academic and familial challenges that she encountered while attending U.S. schools. Through this case study, the authors discuss the issues immigrant high school students experience and present cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…The present study provides potential directions to identify potential clients, like those students who perceived their parents displaying high levels of career-related engagement and over-controlling parenting practices. Moreover, the present study highlights the importance of strengthening school-family partnerships, which may provide students with parental career involvement and autonomous support for their adolescent kids, which may ultimately facilitate students’ CDSE (Watkinson and Hersi, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…The present study provides potential directions to identify potential clients, like those students who perceived their parents displaying high levels of career-related engagement and over-controlling parenting practices. Moreover, the present study highlights the importance of strengthening school-family partnerships, which may provide students with parental career involvement and autonomous support for their adolescent kids, which may ultimately facilitate students’ CDSE (Watkinson and Hersi, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, a meta-analysis of the effectiveness of 153 school counseling interventions found a small to moderate effect size of d = .30, indicating that students who received school counselor interventions have measurably higher outcomes across cognitive, behavioral, and affective domains than students who do not receive those interventions (Whiston et al, 2011). School counseling services have also proven effective for a range of more specific issues and goals, from supporting immigrant students’ career development (Watkinson & Hersi, 2014) to reducing the achievement gap by increasing the academic achievement of African American high school students (Bruce, Getch, & Ziomek-Daigle, 2009). The broad finding is clear: Counseling in schools is an effective way to address a range of student issues (Reback, 2010; Whiston et al, 2011).…”
mentioning
confidence: 99%
“…Data collected postintervention indicated that participation in the group resulted in an approximately 10% increase in grade point average (GPA) and a statistically significant increase in a self-esteem assessment (Steen et al, 2018). Watkinson and Hersi (2014) addressed ways to meet the college and career needs of immigrant-origin students in a case study based on qualitative data derived from a larger study. Among the authors' recommendations to school counselors were hosting college and career information nights (Tier 1) that are responsive to immigrant families' schedules and linguistic needs.…”
Section: Supporting Immigrant-origin Studentsmentioning
confidence: 99%
“…Analysis. By utilizing their knowledge of student cultural assets, school counselors can intentionally work to increase immigrant-origin students' access to career development opportunities like school-wide career events (Watkinson & Hersi, 2014). Collaborating with Wei's family is important because researchers have found that support from parents positively predicted career goals for Chinese immigrant-origin high school students (Ma & Yeh, 2010).…”
Section: Aspirational Capitalmentioning
confidence: 99%